Set up and application of an underwater Α-ray spectrometer for radioactivity measurements - TSABARIS, C.; VLACHOS, S.; PAPADOPOULOS, C.T.; VLASTOU, R.; KALFAS, C.A. (Mediterranean Marine Science, 2005)
The set up and control of an underwater measuring instrument for radioactivity pollution in the marine environment is described. The detection system is based on a NaI scintillator (RADAM III) with modifications for use in the marine environment with on-line measurements. The system is simple, has low power consumption and is stable for long-term monitoring (10 months). Before its deployment, the sensor was calibrated in the laboratory in a tank full of water to reproduce the marine environment. The calibrations were performed, by detecting the 661keV and 1461 keV gamma rays of known activity liquid sources 137 Cs and 40 K, respectively. The measured spectra in the laboratory were compared with spectra from a similar detector as acquired in the field. The analysis of the parallel measurement gave satisfactory agreement for the concentration of the potassium (40 K), as calculated from the salinity in the seawater, thus enabling the system for quantitative measurement of the seawater radioactivity.